Increased lipoxin B4 levels in children with atopic dermatitis - Himmet Haluk Akar; Mikdat Yildiz (Paediatrica Indonesiana, 2019)
Background Atopic dermatitis (AD) is the most common chronic inflammatory skin disease in the pediatric population. The pathophysiology of AD is complex and not clearly understood. The role of lipoxin B4 (LXB4), an anti-inflammatory mediator, has not been sufficiently investigated in children with AD to our knowledge. Objective To compare the levels of serum LXB4 between children with AD and healthy controls. Methods Three groups of children were enrolled in this study: a SPT-Pos group (skin prick test positive 21 subjects with AD), a SPT-Neg group (skin prick test negative 22 subjects with AD), and a control group (23 healthy subjects). Subjects’ serum LXB4 levels of were measured with an ELISA technique. Also, eosinophil counts and total immunoglobulin E (IgE) levels were compared among all groups. Results We observed significantly higher LXB4 levels in AD patients than in controls. Also, LXB4 levels were significantly higher in the SPT-Pos group than in the SPT-Neg group and control group. However, no significant difference was observed between the SPT-Neg and control groups. Conclusion The LXB4 may have an anti-inflammatory mediator role in the pathogenesis of AD in children. The LXB4-associated pathways may be considered in the development of novel therapeutic approaches for the treatment of patients with AD.